Articulation Methods to Increase Student Understanding in Balaghah Learning - Machrup Eko Cahyono; Nurul Musyafa’ah; Muhammad Afthon Ulin Nuha; Muh. Sabilar Rosyad (STUDI ARAB, 2022)
The purpose of this study was to describe the application of the articulation learning method, increase students' understanding of the articulation learning method, and find out the supporting and inhibiting factors of the articulation learning method in the Balaghah subject at Hasbullah Bahrul Ulum Tambakberas Islamic Boarding School, Jombang. This research uses a descriptive qualitative approach with the type of field research. Techniques in data collection are used in the form of observation, interviews, and documentation. This study uses data analysis through condensation, presentation, and conclusion. The research results obtained by the researchers showed that (1) the implementation of the articulation learning method in increasing students' understanding at the Hasbullah Bahrul Ulum Tambakberas Jombang Islamic Boarding School went through three stages, namely the initial stage, the core stage, and the closing stage; (2) in increasing the understanding of the students experienced a significant increase, the data was taken from the learning evaluation; (3) factors supporting the implementation of the articulation learning method include supporting infrastructure, namely the completeness of Islamic boarding school facilities and infrastructure, complete learning books, while the inhibiting factors for the implementation of the articulation learning method differ in the characteristics and level of understanding of each student.